2010
DOI: 10.1021/jp100343d
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Films and Ribbons for Sensing of O2, and 100 ppm of CO and NO2 in Practical Conditions

Abstract: Graphene films and ribbons were grown on Ni-coated Si substrates using the microwave plasma enhanced chemical vapor deposition method. We report the structure, morphology, and quality of graphene films and ribbons. The semiconducting nature of the CVD-grown graphene was observed by studying resistance−temperature variation in the range 25 to 200 °C, using the four-point probe method. Graphene exhibited an increase of resistance upon exposure of CO and a decrease in resistance upon pure O2 and NO2 exposures. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
108
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(111 citation statements)
references
References 28 publications
3
108
0
Order By: Relevance
“…Graphene has also been successfully used in chemical sensors for the identifi cation of similar gases and vapors. [58][59][60][61][62] Whereas graphene and CNTs allow room-temperature operation of chemiresistors, FETs, or other sensor variations, metal oxide materials, even in the form of nanowires, mostly require operation at elevated temperatures ( ∼ 200°C) to obtain comparable sensitivities and response times. 63 Our group has been developing SWCNT-based chemical sensors for nearly a decade.…”
Section: Chemical Sensorsmentioning
confidence: 99%
“…Graphene has also been successfully used in chemical sensors for the identifi cation of similar gases and vapors. [58][59][60][61][62] Whereas graphene and CNTs allow room-temperature operation of chemiresistors, FETs, or other sensor variations, metal oxide materials, even in the form of nanowires, mostly require operation at elevated temperatures ( ∼ 200°C) to obtain comparable sensitivities and response times. 63 Our group has been developing SWCNT-based chemical sensors for nearly a decade.…”
Section: Chemical Sensorsmentioning
confidence: 99%
“…With that goal in mind, many researchers have developed high-performance NO 2 gas sensors using reduced graphene oxide sheets, obtained from high temperature annealing [9] or a chemical conversion with hydrazine [10] and ascorbic acid [11], for application as a low-cost, simple and practical sensor device. More recently, Joshi et al [12] reported a NO 2 gas sensor based on graphene films and ribbons grown on Ni-coated Si substrates using the microwave plasma enhanced chemical vapor deposition (MPECVD) method. In spite of the potential advantages of the CVD-grown graphene films for novel gas sensors, their sensitivity and response time was relatively weak and not yet DOI: http://dx.doi.org/ DOI:10.5714/CL.2013.14.…”
Section: Introductionmentioning
confidence: 99%
“…Since the sensing process of such sensor involves adsorption/desorption phenomena and deprotonation at the interface, the large specific surface area of gas sensing materials is crucial to maintain their high sensing performance. 24 2) The rGO sheets provide high carriers mobility at room temperature, which results in the rapid increase of the hybrid resistance, that is, reduces the response time of hybrid toward NH3 gas; 25 3) When rGO sheets expose to NH3 gas, it will cause decrease in the number of charge carriers due to the electron withdrawing nature of absorbed water, which induce hole-like carriers, 26 resulting in an increase in resistance, thus increasing the sensitivity to NH3 gas 26 ; 4) The electron transfer may occur between the conjugated PANI and rGO through π-π interaction during the sensing process, and consequently increases the sensing performance of hybrid. 27 However, detailed understanding for the role of rGO in the sensing mechanism of hybrid is still lacking.…”
mentioning
confidence: 99%